1996
DOI: 10.1177/089443939601400111
|View full text |Cite
|
Sign up to set email alerts
|

Social Knowledge and Systems Development

Abstract: Information systems contain within them assumptions about how people work and think. Effective use of information technology in work settings requires a full understanding of the specialized knowledge of the work being supported. As the National Information Infrastructure is developed and deployed, there is needed a similar understanding of how its various user communities function in their work and daily lives.The issues I raise here are from the perspective of how social science can contribute to the design,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Studies show that the politics and dynamics of the workplace rather than "technological exigencies" shape outcomes of technology use and therefore patterns of work (Fleck, Webster, & Williams, 1990). Similarly, studies of information technologies in farming stress workplace culture, gendered interactions, and communications as keys to understanding gender and technology (e.g., Grace, Lundin, & Daws, 1996;Leeuwis, 1993;Sachs, 1996). For example, Grace et al (1996) found that "rural women interact with communication technologies in ways which are significantly different from men and from urban women" (p. 64).…”
Section: The Promise Of Liberation? Information Technologies and Gendermentioning
confidence: 96%
See 1 more Smart Citation
“…Studies show that the politics and dynamics of the workplace rather than "technological exigencies" shape outcomes of technology use and therefore patterns of work (Fleck, Webster, & Williams, 1990). Similarly, studies of information technologies in farming stress workplace culture, gendered interactions, and communications as keys to understanding gender and technology (e.g., Grace, Lundin, & Daws, 1996;Leeuwis, 1993;Sachs, 1996). For example, Grace et al (1996) found that "rural women interact with communication technologies in ways which are significantly different from men and from urban women" (p. 64).…”
Section: The Promise Of Liberation? Information Technologies and Gendermentioning
confidence: 96%
“…Instead, attention is drawn to technological design and its relation to knowledge, problem solving, and culture. Patricia Sachs (1996) argued that technology systems contain assumptions about how people work and think. She recommended that we need more specific empirical information about "how people in work communities collaboratively solve problems and how various forms of social organization support or constrain their ability to do so" (p. 36).…”
Section: The Promise Of Liberation? Information Technologies and Gendermentioning
confidence: 99%